2010
DOI: 10.5585/remark.v9i2.2174
|View full text |Cite
|
Sign up to set email alerts
|

A Importância Estratégica dos Relacionamentos de Negócios em Redes de Empresas: Uma Visão Baseada no Rbv - Resource Based View

Abstract: Esse trabalho visa discutir a importncia dos relacionamentos estratgicos de negcios de forma cooperativa, pois se tm tornado um importante antecedente de sucesso nos negcios. Estudos mostram que alianas e parcerias possuem um importante papel na moldagem das vantagens competitivas baseadas em recursos da empresa. Para a concretizao dos objetivos propostos nesse estudo, iniciou-se uma investigao em duas redes imobilirias e adotou-se como pilar metodolgico, a tipologia qualitativa de investigao, por fornecer a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
2
0
5
Order By: Relevance
“…These authors identified the potential maximization of competitiveness in real estate companies, as a result of often making transactions in partnerships, and operating in network settings. According to Alves et al (2010), integration in real estate networks allows participating companies to pool their resources, which are comprised mainly of their respective client and estate portfolios.…”
Section: Literature Review and Theoretical Background On Business Netmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors identified the potential maximization of competitiveness in real estate companies, as a result of often making transactions in partnerships, and operating in network settings. According to Alves et al (2010), integration in real estate networks allows participating companies to pool their resources, which are comprised mainly of their respective client and estate portfolios.…”
Section: Literature Review and Theoretical Background On Business Netmentioning
confidence: 99%
“…Frequent interaction amongst decisionmaking agents allows the development of trust, resulting in adherence to the trust development model introduced by Rousseau et al (1998). However, as shown in the studies from Alves et al (2010) and Gulati and Nickerson (2008), the shared mode of governance encounters boundaries in network expansion and development, which many times lead to the existence of more bureaucratic and centralised structures.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…Preocupadas com a necessidade de atualização de seu modelo de gestão para maior competitividade, as imobiliárias independentes passaram nos últimos anos a buscar modelos organizacionais alternativos, dentre os quais se destaca a integração em redes de negócios (ALVES et al, 2010).…”
Section: Contexto De Realização Da Pesquisa -Mercado Imobiliáriounclassified
“…A unidade de pesquisa é a imobiliária respondente que participou de transações em parceria Em redes imobiliárias, como observado por Alves (2010), o ganho em competitividade proporcionado pela atuação em rede se perfaz mediante a possibilidade de melhor combinação dos recursos das firmas participantes, constituídos principalmente pelas respectivas carteiras de clientes e imóveis.…”
Section: Unidade De Pesquisaunclassified
See 1 more Smart Citation